To the theory of spin–charge separation in one-dimensional correlated electron systems - Zvyagin, A.A. (Физика низких температур, 2004)
Spin—charge separation is considered to be one of the key properties that distinguish low-dimensional
electron systems from others. Three-dimensional correlated electron systems are described
by the Fermi liquid theory. There, low-energy excitations (quasiparticles) are reminiscent
of noninteracting electrons: They carry charges e and spins 1/2. It is believed that for any one-dimensional
correlated electron system, low-lying electron excitations carry either only spin and no
charge, or only charge without spin. That is why recent experiments looked for such low-lying collective
electron excitations, one of which carries only spin, and the other carries only charge. Here
we show that despite the fact that for exactly solvable one-dimensional correlated electron models
there exist excitations which carry only spin and only charge, in all these models with short-range
interactions the low-energy physics is described by low-lying collective excitations, one of which
carries both spin and charge.